2015
DOI: 10.1007/s00330-014-3581-3
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Index of Shape (SIS): a quantitative DCE-MRI parameter to discriminate responders by non-responders after neoadjuvant therapy in LARC

Abstract: • DCE-MRI shape descriptors are investigated to assess preoperative CRT response in LARC. • Identification of the best TIC shape descriptors combination through a linear classifier. • Identification of a single MRI index to predict neoadjuvant treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 42 publications
(72 reference statements)
4
51
0
Order By: Relevance
“…These results are comparable with the findings reported in our previous paper [13] where ΔSIS percentage variation obtained a sensitivity of 93.5% and a specificity of 82.1%. ΔSIS showed a statistically significant difference in median values for responder and non-responder patients based on TRG and pathological T stage.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are comparable with the findings reported in our previous paper [13] where ΔSIS percentage variation obtained a sensitivity of 93.5% and a specificity of 82.1%. ΔSIS showed a statistically significant difference in median values for responder and non-responder patients based on TRG and pathological T stage.…”
Section: Discussionsupporting
confidence: 92%
“…The heterogeneity in the neoadjuvant treatment scheme with the majority of study population receiving an experimental schedule of “antiangiogenic” agent plus oxaliplatin in comparison of standard CRT scheme was previously investigated in the our study [13]. The analysis in [13] showed that the treatment schedule did not influence the proportions in responder and non-responder patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…[29][30][31][32] However, the acquisition and evaluation of these additional sequences demand more resources, prolonged scan time and additional time for interpretation. Aiba et al 17 found that the addition of 18 F-FDG PET to MRI volumetry did not improve the performance of NACT response assessment.…”
Section: Discussionmentioning
confidence: 99%